2021
DOI: 10.1016/j.jbc.2021.100884
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 activation is not sufficient to suppress hepatic PPARα signaling or ketogenesis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…At the peak, S6 phosphorylation was comparable between fed and unfed states. Thus, the induction of mTORC1 was not sufficient to suppress blood βOHB, which is in agreement with the results from reference ( 45 ) and suggests that additional mechanisms must be involved in the regulation of βOHB rhythms.…”
Section: Resultssupporting
confidence: 91%
“…At the peak, S6 phosphorylation was comparable between fed and unfed states. Thus, the induction of mTORC1 was not sufficient to suppress blood βOHB, which is in agreement with the results from reference ( 45 ) and suggests that additional mechanisms must be involved in the regulation of βOHB rhythms.…”
Section: Resultssupporting
confidence: 91%
“…Finally, under ketogenic conditions, liver morphology and ketone levels in mice lacking hepatocyte p110α do not differ from those of control mice, contrasting the idea that defective p110α signaling is associated with altered FFA uptake by hepatocytes (Chattopadhyay et al, 2011). Thus, in accordance with our previous observations from the lab and others, these results support the notion that autonomous regulation of PPARα activity through the insulin/PI3K/Akt/mTORC1/S6K pathway is minimal in comparison to the induction via adipose tissue lipolysis during fasting periods (Fougerat et al, 2022; Montagner et al, 2016; Régnier et al, 2018; Selen and Wolfgang, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…7K ). Noteworthy, previous studies directly tested whether enhanced mTORC1 activity in the liver (i.e., in parenchymal and non-parenchymal cells) 10 , 16 or specifically in hepatocytes 58 is sufficient for suppressing ketogenesis in a physiological context (i.e. following prolonged fasting).…”
Section: Discussionmentioning
confidence: 99%
“…following prolonged fasting). Interestingly, while enhanced mTORC1 activity in the liver is able to suppress fasting-induced ketogenesis its overactivity only in hepatocytes failed to achieve this effect 10 , 16 , 58 . Our assessment of the results from the aforementioned three studies in combination with our data shown herein would shift the focus from the ketogenic-suppressing role of mTORC1 in hepatocytes (as previously thought and debated) 58 to mTORC1 in non-parenchymal hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation